Walking energetics and fatigue are associated with physical activity in people with knee osteoarthritis. (August 2021) - Foucher, Kharma C.; Aydemir, Burcu; Huang, Chun-Hao
Abstract: Background: Aberrant biomechanics may influence osteoarthritis-associated physical activity limitations. Our purpose was to evaluate the association of walking energetics, fatigue, and fatigability on physical activity in people with knee osteoarthritis. We hypothesized that using increased energy for walking, experiencing more fatigue, or being more fatigable are associated with less activity, and that fatigue and fatigability mediate the relationships between walking energetics and physical activity. Methods: We tested our hypothesis in 30 people with knee osteoarthritis (age 58 ± 9 years, 10 Male/20 Female). Physical activity was assessed using the University of California Los Angeles score. We used a six-minute walk test to predict VO2 max. Next we used a portable oxygen exchange system to measure relative energy used (100 * VO2 rate/VO2 max) and VO2 cost during walking at preferred speeds. We used the Knee injury and Osteoarthritis Outcome Score subscale to quantify pain, and the Patient Reported Outcome Measurement Instrument System Fatigue survey and a treadmill-based fatigability test to assess fatigue and fatigability. Spearman correlations, regression, and mediation analysis were used to test our hypotheses. Findings: Greater energy used during walking, fatigue, and fatigability were all associated with lower physical activity (rho = −0.585 to −0.379, P = 0.001 to 0.043). These associations persisted when incorporating pain into the models. Fatigue and fatigability mediated the associations between walking energetics and physical activity. Interpretation: Walking energetics could be a useful target to promote physical activity in people with osteoarthritis. Further, the effect of walking energetics on physical activity may work through its impact on fatigability. Highlights: This study concerned physical activity limitation in knee osteoarthritis. Higher energy use during walking was associated with lower physical activity. More fatigue or fatigability were associated with lower physical activity. Fatigability mediated the association between energetics and physical activity. Findings were in keeping with the pain-energy model of activity limitation.